Development of junior football skills test based on validity and reliability through expert judgment - Subagyo Irianto; Tomoliyus Tomoliyus; Awan Hariono; Yulvia Miftachurochmah; Hary Widodo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: This study aimed to develop a reliable and valid junior football skills test through expert judgment.